Farmers' control practices against the invasive red spider mite, Tetranychus evansi Baker & Pritchard in Benin. (October 2015) - Azandémè-Hounmalon, Ginette Y.; Affognon, Hippolyte D.; Komlan, Françoise Assogba; Tamò, Manuele; Fiaboe, Komi K.M.; Kreiter, Serge; Martin, Thibaud
Abstract: In 2008, the invasive tomato red spider mite Tetranychus evansi (Acari: Tetranychidae), a pest of solanaceous crops, was identified for the first time as the cause of serious damage on tomato ( Solanum lycopersicum L.; Solanaceae) crops in Benin. Since then, frequent outbreaks have been observed on Solanaceae and other leafy vegetables such as purple amaranth ( Amaranthus cruentus L.; Amaranthaceae) and bitter leaf ( Vernonia amygdalina D.; Asteraceae) in all growing areas in southern Benin. The objective of this study was to evaluate the intensity of damage by this invasive pest and the impact of farmers' control practices on purple amaranth, African eggplant (Solanum macrocarpon L. ; Solanaceae) and tomato crops. A survey was carried out in January 2013 among 150 farmers in the three major growing areas in southern Benin: Sèmè-Kpodji, Grand-Popo and Pahou. Tetranychus evansi was the only mite observed, causing production losses estimated at 65% for African eggplant, 56% for tomato and 25% for purple amaranth. Previously encountered species such as Tetranychus urticae Koch, Tetranychus ludeni Zacher (Acari: Tetranychidae) and Polyphagotarsonemus latus Banks (Acari: Tarsonemidae) were not observed in any of the 45 samples. To protect the infested crops, growers sprayed various synthetic pesticides at high frequencies according to crop phenology 3, 6 and 12 times per month, respectively, on purple amaranth, African eggplant and on tomato, on average. The most frequently used pesticides were pyrethroids and organophosphate compounds. Farmers reported that these compounds were largely ineffective against T. evansi . The risks posed to human and environmental health, as well as existing alternatives to chemical pesticide use, are discussed.